Analysis of evaporation and thermal decomposition of ionic liquids by thermogravimetrical analysis at ambient pressure and high vacuum - Heym, Florian; Etzold, Bastian; Kern, Christoph; Jess, Andreas (Green Chemistry, 2011)
Ionic liquids (ILs) are widely discussed as alternative green solvents not only because of their unique chemical properties, but also because of their extremely low vapour pressure and – at least in some cases – relatively high thermal stability. Two complementary methods are analyzed and compared to determine both the rate constant of decomposition and the vapour pressure of four ILs: (1) thermogravimetrical analysis at ambient pressure (TGap) with an overflow of inert gases, and (2) high vacuum (HV) experiments with a magnetic suspension balance (MSB). At ambient pressure, [EMIM][MeSO3] and [EMIM][CF3SO3] decompose without a significant contribution of evaporation, which leads to the rate constant of thermal degradation. For both ILs, the vapour pressure can only be determined at HV by the MSB, because the evaporation rate is then higher than the decomposition rate. For the relatively volatile ILs [EMIM][NTf2] and [BMIM][NTf2] the vapour pressure can be derived both by the MSB at HV as well as by TGap. General strategies to determine the volatility and stability of ILs and criteria for the maximum operation temperature with regard to decomposition and evaporation are presented. © 2011 The Royal Society of Chemistry.
CRIS-Team Scopus Importer:2023-08-15